Metode Langsung Dalam Pengajaran Bahasa Arab - Asriyah Asriyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
The method of teaching arabic as a second language has much progress following the development of language teaching mathod. In its history, direct method is the oldest method applied in teaching language after qawa‘id-tarjamah. This writing explored the history of direct method as counter to previous methods. This method assumes that language teaching-learning process is like teaching-learning mother languag that is by using language directly. Thus, language become active and dinamic